(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
Project thinking in design deals with diverse information, among which: subjective information that acts in the cultural construct of complex social interactions, and that will serve the designer as a connection between the product and the consumer. This research aimed to analyze fashion design methodologies and develop useful tools for the fashion designer’s creative process. It was done with a theoretical approach, from the theoretical framework, and practice, through a survey applied in August 2020, with 5 professionals from different areas of fashion, from different cities of Santa Catarina, to verify the use of methods and tools recognition of symbolic references in fashion. This research was constituted by the interdisciplinary approach, uniting semantics, semiotics, and cognitive ergonomics, in the search for tools and methods to aid in the designer’s interpretive process, and to contribute to interdisciplinarity and interpretive systematization in design thinking. We sought to recognize methodologies applied in the Product Development Process (PDP), the tools used or recognized, and the semantic references of fashion. The result is the synthesis of the PDP for fashion design, the useful tools coming from the semiotic theory of Peirce (2005), and Greimas (1984), and from the semantic memory of Mervis & Rosch (1987). The observation of the need for interpretive tools culminated in the elaboration of cards of aesthetic, symbolic and fashion style references, to serve as tools, and constitute themselves as a method. On the data obtained, the content analysis methodology was used (BARDIN, 2016).